Up-regulated GRB7 protein in gastric cancer cells correlates with clinical properties and increases proliferation and stem cell properties - Pei, Yuan-yuan; Ran, Jian; Wen, Lijuan; Liu, Xiaoyi; Xiang, Li; Liu, Weiqiang; Wei, Fengxiang (Frontiers in Oncology, 2023)
It has been reported that GRB7 is closely related to a variety of human solid tumors, but its role in gastric cancer has not been reported yet. The purpose of this study was to investigate the expression level and intracellular effects of GRB7 in human gastric cancer. Through real-time fluorescent quantitative PCR and Western blot, we found that the expression of GRB7 in gastric cancer cell lines was higher than that of the corresponding normal gastric epithelial cells, and correspondingly higher in gastric cancer tissues than its paired adjacent tissues. The immunohistochemical staining of 210 cases of gastric cancer and adjacent tissues verified that GRB7 protein was expressed more highly in cancer tissues than in adjacent tissues. SPSS analysis also showed that GRB7 protein expression levels were positively correlated with the clinical stage of gastric cancer patients, and also with The prognosis of patients is negatively correlated. GSEA analysis of GRB7 mRNA levels in gastric cancer tissues and normal gastric epithelial tissues from public databases showed that GRB7 may affect cell proliferation and related processes of intracellular stem cells. Stable gastric cancer cell lines with high expression of GRB7 and low expression of GRB7 were established to verify the results of GSEA analysis. MTT experiments, clone formation experiments and cell cycle flow cytometry experiments have verified that GRB7 can promote the proliferation of gastric cancer cells. Balloon formation experiments and lateral subpopulation cell sorting experiments also show that GRB7 is positively related to the self-renewal ability of gastric cancer stem cells. This study shows that GRB7 molecules highly expressed in gastric cancer tissues can promote the proliferation of gastric cancer cells and increase the proportion of gastric cancer stem cells, so it is expected to become a diagnostic molecule or potential therapeutic target for gastric cancer.